1996
DOI: 10.1021/ja9605984
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Group IIIA and Lanthanide Metals by Hexahomotrioxacalix[3]arene Macrocycles

Abstract: The hexahomotrioxacalix[3]arene macrocycles 1 are observed to bind trivalent metals (Sc3+, Lu3+,Y3+, La3+) more strongly than alkali metal ions (Li+, Na+, K+). Complexes of macrocycle 1a with Lu(III) (3), Y(III) (4), and La(III) (5) have been structurally characterized to be μ-aryloxo-bridged dimers with the formula [M(L)(DMSO)]2 (M = Lu, Y, La; L = trianion of macrocycle 1a). Periodic trends in the structures and dynamic behavior of the complexes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…The La(L) complex is structurally similar to that previously reported for the La complex of /?-te^butylhexahomotrioxacalix [3]arene (14) (10) The La centers in complexes 4 and 14 are coordinated to the three phenolic oxygen atoms and the three ring heteroatoms (Ο, N). For complex 4, the complex possesses a tricapped trigonal prismatic structure where the remaining coordination sites are occupied by the ester carbonyl groups.…”
Section: Isolation Of Group 3 Metal-ion Complexes Of the Azacalix[3]asupporting
confidence: 82%
“…The La(L) complex is structurally similar to that previously reported for the La complex of /?-te^butylhexahomotrioxacalix [3]arene (14) (10) The La centers in complexes 4 and 14 are coordinated to the three phenolic oxygen atoms and the three ring heteroatoms (Ο, N). For complex 4, the complex possesses a tricapped trigonal prismatic structure where the remaining coordination sites are occupied by the ester carbonyl groups.…”
Section: Isolation Of Group 3 Metal-ion Complexes Of the Azacalix[3]asupporting
confidence: 82%
“…The data obtained in [32] indicate that degree of cupping increased with growing metal ion whereas the µ-aryloxy bonds weakened.…”
Section: Receptor Properties Of Hexahomotrioxacalix[3]arenes With Frementioning
confidence: 94%
“…The study of NMR spectra of complexes 3335 in toluene-d 8 [32] revealed their fluxional behavior. The spectral data indicate that in 35 in toluene-d 8 occurred a rupture of a m-aryloxy bond followed by rotation around the remaining µ-aryloxy bond.…”
Section: Receptor Properties Of Hexahomotrioxacalix[3]arenes With Frementioning
confidence: 98%
See 2 more Smart Citations